Begonia makuruyot (Begoniaceae, section Baryandra), a new species from Surigao del Norte Province, Philippines - Rule, Mark Gregory Q.; Ang, Yu Pin; Rubite, Rosario R.; Docot, Rudolph Valentino A.; Bustamante, Rene Alfred Anton; Robinson, Alastair S. (Phytotaxa, 2020)
A new Begonia species, Begonia makuruyot, from B. section Baryandra is described and illustrated from forests over limestone in Surigao del Norte. This distinctive species, which appears to be endemic to the type locality, inhabits shaded limestone walls along the Daywan River at an elevation of 10–50 metres above sea level. Begonia makuruyot is distinguished from other Philippine Begonia by its rugose laminae, pendent leaves, pilose petioles and stipules fused with fleshy, aristate trichomes that are occasionally branching. A comparison with the phenetically similar B. acuminatissima is provided. Based on IUCN Red List criteria, B. makuruyot is designated Critically Endangered (CR).